2014
DOI: 10.1016/j.electacta.2014.04.038
|View full text |Cite
|
Sign up to set email alerts
|

Charge–discharge behavior of a Na2FeP2O7 positive electrode in an ionic liquid electrolyte between 253 and 363 K

Abstract: The electrochemical properties of a Na 2 FeP 2 O 7 positive electrode were investigated in the ionic liquid sodium bis(fluorosulfonyl)amide (NaFSA)-N-methyl-N-propylpyrrolidinium bis(fluorosulfonyl)amide (C 3 C 1 pyrrFSA). A stable charge-discharge behavior was obtained over the temperature range 253-363 K. The cell offered nearly a one-electron theoretical capacity of about 90 mAh g −1 at 298-363 K. The rate capability showed considerable enhancement with increasing temperature, delivering 50 mAh g −1 at a ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 60 publications
7
48
0
Order By: Relevance
“…24,28 The positive electrode was prepared by mixing Na 2-x Fe 1+x/2 P 2 O 7 , acetylene black and polytetrafluoroethylene in a weight ratio of 75:20:5. The mass loading and thickness of the active material were around 2.0 mg cm -2 and 50 μm, respectively.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24,28 The positive electrode was prepared by mixing Na 2-x Fe 1+x/2 P 2 O 7 , acetylene black and polytetrafluoroethylene in a weight ratio of 75:20:5. The mass loading and thickness of the active material were around 2.0 mg cm -2 and 50 μm, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…20,21 However, the adoption of IL electrolytes for Na batteries has received less attention so far. 22,23 In our previous studies, the charge-discharge behavior of Na 2 FeP 2 O 7 electrodes in Na[FSA]-[C 3 C 1 pyrr][FSA] (where FSA = bis(fluorosulfonyl)amide and C 3 C 1 pyrr = N-methyl-Npropylpyrrolidinium) IL electrolytes was investigated over a wide temperature range of 253-363 K. 24 The results revealed a considerable enhancement in rate capability with increasing temperature along with an outstanding cyclability, implying that there are significant opportunities to improve the performance of Na secondary batteries by utilizing an IL electrolyte. Another advantage of using IL electrolytes is that the operation of the batteries at high temperatures is favorable to fully draw the potential capacity of the electrode material.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11] Sodium is abundant in the crust and seawater, showing a relatively low standard redox potential (¹2.71 V vs. SHE). Thus, batteries with low cost and high energy density can be constructed.…”
Section: Introductionmentioning
confidence: 99%
“…The semicircle at the middle frequency corresponds to the electrochemical reaction process which includes both positive and negative electrode reactions. 21,22 The electrochemical reaction resistance (R ER ) largely increases with lowering the operating temperature, indicating a significant sensitivity to temperature. ) and Q (E a = 23.7 kJ mol ¹1 ), which supports that R ³ is due to the electrolyte resistance.…”
Section: ¹1mentioning
confidence: 99%
“…More importantly, the value of R ER is much larger than that of R ³ , which indicates that the total cell resistance is mainly governed by R ER . In our previous study, 21 the impedance of Na/Na symmetric cell was measured at different temperatures, which revealed that the major component of R ER originates from the Na metal electrode, especially at lower temperatures. Thus, it is concluded that the drastic decrease of capacity at lower temperatures in the present study is mainly caused by the higher R ER of Na counter electrode.…”
Section: ¹1mentioning
confidence: 99%